An experimental study on the effectiveness of fire warnings on evacuation from a metro train: The response phase. (15th June 2022) - Li, Xiaolian; Huang, Zhongyi; Fang, Zhiming; Huang, Yiming; Lv, Wei; Ye, Rui; Cao, Shuchao
Abstract: Voice alarms play an important role in the evacuation of metro systems, while few studies focus on voice alarms inside train carriages. In this study, the effect of a fire warning on the initial phase of evacuation in a carriage is investigated. Both a questionnaire investigation and evacuation experiments with different fire voice alarms in a metro train model were conducted to quantitatively analyze the behaviors of evacuees during the response phase of evacuation. According to the analysis of the questionnaire, the response time calculated from the danger signal (smoke) is suitable for assessing the evacuees' response during the response phase. As indicated by the Pearson correlation coefficient between the minimum and mean response times (0.96), the first person's response has a significant influence on the behaviors of other evacuees. Moreover, comparisons among different categories of experiments demonstrate that the danger signal (smoke), fire alarm bell, and 3–4 units of a voice alarm with a normal and comfortable tone can deliver effective information to evacuees during the initial phase of evacuation. In addition, the effect of a voice alarm with an urgent and fast tone still needs further investigation. The results can help design fire voice alarms and improve the efficiency of evacuation in metro systems.